PERHITUNGAN TAKSIRAN NILAI PERSEDIAAN PADA MINIMARKET MANNA MANDIRI GKI ELIM TEMPAT GARAM - Pangkereg, Cristian; Muda, Markus Muda; Mambrasar, Mardila (Jurnal Pitis AKP, 2022)
The purpose of research at the Manna Mandiri Minimarket Sorong is to determine the final inventory value by calculating the estimated inventory value. Better inventory research can increase profits or profitability. Meanwhile, poor inventory valuation can erode profits and become a less competent business. Inventory is useful for protecting the company from unexpected events and disruptions in its operations. Based on the evaluation, it can be concluded that the estimation method that can be used to assess inventory is the Retail Inventory Method which uses a physical calculation system for recording inventory that is held to be able to provide initial inventory information (if any) both according to cost and selling price. Purchases for the respective period are based on the cost price and the diluted selling price, adjustments or changes in selling prices that occur in the relevant period, and information on the results.